2002
DOI: 10.1063/1.1431427
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the structural phase transformations in epitaxial YHx switchable mirrors

Abstract: Geometric-shape-dependent structural transition behavior in (110) SrRuO3 epitaxial thin films Structure and strain relaxation mechanisms of ultrathin epitaxial Pr 2 O 3 films on Si(111) J. Appl. Phys. 97, 074906 (2005); 10.1063/1.1883304Switchable yttrium-hydride mirrors grown on CaF 2 (111): A x-ray photoelectron spectroscopy and diffraction studyThe detailed mechanisms of the structural phase transformations that occur in epitaxial Y-hydride switchable mirrors are revealed with high resolution transmission e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…[23]). This suggests that ridges contribute to the electrical transport properties of the as-deposited epitaxial Y film, since they are crystalline with the c-axis situated in-plane of the film [9]. Upon H absorption, the anisotropy ratio η(T ) increases (see in Table 2).…”
Section: Ridgesmentioning
confidence: 96%
See 2 more Smart Citations
“…[23]). This suggests that ridges contribute to the electrical transport properties of the as-deposited epitaxial Y film, since they are crystalline with the c-axis situated in-plane of the film [9]. Upon H absorption, the anisotropy ratio η(T ) increases (see in Table 2).…”
Section: Ridgesmentioning
confidence: 96%
“…Using transmission electron microscopy (TEM), Kooi et al showed that the ridges are crystalline with the caxis almost in-plane [9]. They result from {1 0 1 2} deformation twinning [9]. Remarkably, the ridges act as a barrier for lateral H diffusion and as a sort of microscopic lubricant for the domain switching.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Here, the stress is relaxed along specific crystallographic planes resulting in characteristic morphology changes (triangles, see Figure 7). [84,10,85] At lower stress and strong adhesion, the stress is elastically relaxed. We will discuss first this case of strong adhesion, where the film stays attached to the substrate and the morphology remains basically unchanged (elastic strain relaxation), and then discuss the case of weak adhesion.…”
Section: Adhesion and Morphologymentioning
confidence: 98%
“…[23] It is at least a showing the interface between metallic yttrium, yttrium dihydride and yttrium trihydride. Although the large volume expansion causes significant morphology changes (so-called Manhattan structure, [84,10,85] ) the thin film remains intact (the figure is taken from ref. [47]).…”
Section: Strong Adhesionmentioning
confidence: 99%